New Media in Facing The Challenges of Cyber Terrorism | الإعلام الجديد في مواجهة تحديات الإرهاب الإلكتروني - Lalu Supriadi Bin Mujib (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
This study examines new media in facing the challenges of cyber terrorism. The study aims to explore: the relationship between terrorism and the media, the reasons leading to the terrorist action, the media's duplication in its dissemination of terrorism news, the role of the National Counter-Terrorism Authority (BNPT), and media strategies in countering of terrorism. The research relies on the descriptive analytical approach, which is based on the literatur review of data collection. That deals with the issue of terrorism, then monitors information on contemporary media, then searches for media policies and strategies to counter terrorism. The results of the research found that the media and terrorism each work to achieve both their interests, because terrorism plans and exploits the media to achieve their goals and at the same time the media benefits from the operations committed by the terrorist group to display them in the newscasts to attract the attention of the public. There are several reasons that led to the emergence of the terrorist idea or terrorist process, namely social deprivation, the absence of social justice, the penetration of the scales of justice in economic exchange, the exploitation of the goods of disadvantaged peoples, the restriction of freedoms and support of totalitarian regimes, the spread of racist engagement and the phenomena of Islamophobia, and distorted understanding of religion. There has been a great debate among the media people themselves in publishing news that pertains to terrorist operations, between those who see them being published to demonstrate their brutality and alienating people from their owners, and those who see reservations about their publication, although many tend to refrain from publishing in the interest of that, which is relying on Islamic values that Terrorist atrocities are not likely to be spread among the general public pursuant to the general Islamic guidance, not to spread badness among the people.